PENGARUH METODE PEMBELAJARAN DAN KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR SEJARAH SISWA SMA NEGERI 27JAKARTA - Nurzengky Ibrahim (Jurnal Ilmiah Mimbar Demokrasi, 2017)
This study aimed to reveal the effect of Emotional Intelligence Learning Method and the History of Student Learning Outcomes SMAN Jakarta. Metode experimental method used is to design treatments by level 2 x 2 with variable outcome variables studied history and learning methods as well as one independent variable 2 emotional intelligence. The results showed (1) The study of high school students who follow the history of learning methods sociodramatic higher than students who take conventional learning methods, (2) there is a significant interaction effect between emotional intelligence learning methods and learning outcomes history of high school students. (3) for students with high emotional intelligence learning methods sociodramatic better learning outcomes than conventional learning methods, and (4) for students who have low emotional intelligence with conventional teaching methods better learning outcomes than learning methods sociodramatic. It can be concluded that the method of teaching sociodramatic can improve learning outcomes for students with a history of high emotional intelligence.